Biossensor amperométrico à base de tirosinase aplicado na determinação de compostos orgânicos em amostras ambientais - Ferreira, Lucas Franco (2005)
An amperometric biosensor based on tyrosinase enzyme was developed and investigated for monitoring of Parathion Methyl, Carbaryl, Carbofuran and Diazinon. The enzyme was immobilized on a cobalt (II) phtalocyanine modified graphite composite electrode (CoPc-GCE) by cross-linking with glutaraldehyde and bovine serum albumin. Several parameters which affect the response of tyrosinase biosensor referring to catechol as substrate were examined. The response of the CoPc-GE towards the catechol was investigated in terms of the detection limit (LOD), response stability and electrode fouling by the of polymeric oxidation products. These parameters were compared with the ones obtained with an unmodified carbon paste electrode (CPE) and a cobalt (II) phtalocyanine modified carbon paste electrode (CoPc-CPE). The CoPc-GCE exhibited the highest LOD to catechol, 1.0 x 10-6 mol L-1. Additionally, this electrode exhibited a stable baseline and a time-independent current intensity. The intensity of the current was approximately unchanged for 65 catechol measurements against 2-3 measurements reported to the others electrodes. Various experimental parameters were explored for optimum analytical performance of the biosensor. The catechol was determined by the direct reduction of biocatalytically liberated o-quinone at 0.20 V vs Ag/AgCl (3.0 mol L-1 KCl). The results showed that highest amperometric responses were found in 0.05 mol L-1 phosphate buffer with 0.1 mol L-1 KCl, and pH 6.50. The linear range for the reported biosensor was 5.0 x 10-5 a 1.0 x 10-3 mol L-1 for catechol. The sensitivity was ca. 1.6 x 10-5 μA mol -1 L. The immobilized enzyme yields specific activities to catechol higher than that of free enzyme. The apparent Michaelis-Menten constant (KM app) value of immobilized enzyme was 1.7 mM while that of soluble enzyme was 2.3 mM. Inhibition studies were carried out by using Methyl Parathion, Diazinon, Carbaryl and Carbofuran, respectively. The decrease of the rate of reduction in the current due to produced o-quinone was used for evaluation. All four compounds showed a linear dependence between the concentration and the relative inhibition. Recovery studies employing the best conditions were carried out by using water samples spiked with the inhibitors at levels of 30 ppb, respectively. The recoveries ranged between 93 % and 99 % with coefficients of variation of 1.01 2.09 %.